Effects of material transfer evolution on tribological behavior in CuCrZr alloy paired with 7075 Al alloy under current-carrying. (January 2023) - Wang, Xing; Yao, Pingping; Li, Yuxing; Zhou, Haibing; Xiao, Yelong; Deng, Minwen; Kang, Li; Zhou, Peiyu
Abstract: This study investigated the effects of material transfer evolution on the tribological behavior of a CuCrZr alloy paired with the 7075 Al alloy under current-carrying using a self-developed block-pin wear tester. The microstructure, material transfer behavior, tribological characteristics, and wear mechanism of the worn surfaces were examined. The results indicated that mechanical and electrical wear were the primary wear mechanisms, and a large amount of the Al alloy material was transferred to the worn surface. The material transfer was caused by the adhesion of debris and the splashing of the Al alloy sample. The material transfer process affected the tribological behavior; the final stable Al alloy layer on the worn surface reduced and stabilized the coefficient of friction. Highlights: Current-Carrying Tribology Behavior of CuCrZr/7075 Alloy pairs was investigated. Understanded the formation mechanism of material transfer. The effect of material transfer on tribological behavior was analyzed.